Bacterial Cellulose-Based Biofilm Forming Agent Extracted from Vietnamese Nata-de-Coco Tree by Ultrasonic Vibration Method: Structure and Properties - Tuan Anh Nguyen; Xuan Canh Nguyen (Journal of Chemistry, 2022)
Bacterial cellulose has recently received more attention in several fields including biology and biomedical applications due to its outstanding physicochemical properties such as thermal stability, biodegradability, good water holding capacity, and high tensile. Cellulose, the most abundant biomolecule on Earth, is available in large amounts in plants. However, cellulose in plants is accompanied by other polymers such as hemicellulose, lignin, and pectin. On the other hand, highly purified bacterial cellulose without impurities is produced by several microorganisms. In which, the most active producer is Acetobacter xylinum. A. This study developed a new process using sonication to isolate bacterial cellulose from nata-de-coco Vietnam. Sonicating time and temperature, two important engineering factors, were considered and discussed (Temperature: 55, 60, 65, 70°C; Time: 15, 30, 60, 90 min). Research results have established that the ultrasonic vibration time of 60 minutes at 65 degrees Celsius gives the best structural properties of BC. The morphology, structural, and thermal properties of the obtained films were investigated by SEM, FTIR, and TGA. Besides, tensile strength was also evaluated. The results show that sonication is not only a favorable technique to isolate cellulose nanofibers but it also enhances their crystallinity.